PROFIL PROFESIONALISME GURU MADRASAH IBTIDAIYAH UNGGULAN DI JAKARTA SELATAN - Hasyim Asy'ari; Asep Ediana Latip (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2014)
Abstract : This study aims at formulating a model of the profile of teachers professionalism of excellent Islamic Primary School (IPS). The source of data of this research is obtained from six excelence IPS in South Jakarta that achieve score of accreditation A.This research is a non experimental research that uses survey method. The population of this research is all teachers in 15 Excelence IPS with the sample as much as 40% of the teachers. as many as 100 teachers. As for the sampling technique used in this research is simple random sampling with descriptive statistics. The result of this research shows that firstly the profile of professionalism of the teachers of excellent IPS in South Jakarta is indicated by adequate teachers competency in personality, pedagogy, professionalism, and social aspect. Secondly, at the dimension of learning community teachers have not fully showed self development as a part of learning community. Thirdly, at the financial dimension it is know that the teachers of especially State Islamic Primary Schools are willing to accept all the policy of reward system set by the goverment and their schools headmasters. Fourtly, the linearity of educational background with the teaching profession. Fifthly, there is no difference in average scores the characteristics of profile of teachers professionalism between Private Islamic Primary Schools and the State ones. DOI: 10.15408/tjems.v1i1.1110